2004
DOI: 10.1007/s00221-004-1890-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory additivity in trigeminal chemoreception as reflected by detection of mixtures

Abstract: A series of experiments probed into the degree of chemosensory detection additivity exhibited by mixtures of ethyl propanoate and heptanoate in terms of their trigeminal detectability via nasal pungency (i.e., irritation) and eye irritation. Nasal pungency was tested in subjects lacking a functional sense of smell (i.e., anosmics) to avoid olfactory biases. First, we built concentrationdetection functions for each chemical and sensory endpoint. Second, we used the data from the functions to prepare mixtures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…At near-threshold levels, we can safely disregard interactions among the mixed chemicals themselves as a factor in dose-and response-addition: Experiments and calculations made on model solvents mimicking the olfactory receptor biophase indicate that interactions between two esters in such a biophase are negligible at the vapor concentrations necessary for odor detection [29]. In fact, even at the much higher vapor concentrations necessary for nasal pungency or eye irritation (i.e., trigeminal) detection [17], the extent of interaction for an ester pair in a biophase is not likely to be more than 1 or 2 % [29]. Albeit the lack of an identical strategy and analysis between the 1-butanol/2-heptanone and the butyl acetate/toluene studies limits a direct comparison, the different chemical contrast between the alcohol and the ketone, compared to that of the acetate and the alkylbenzene, might have driven a dissimilar outcome (cf.…”
Section: Introductionmentioning
confidence: 99%
“…At near-threshold levels, we can safely disregard interactions among the mixed chemicals themselves as a factor in dose-and response-addition: Experiments and calculations made on model solvents mimicking the olfactory receptor biophase indicate that interactions between two esters in such a biophase are negligible at the vapor concentrations necessary for odor detection [29]. In fact, even at the much higher vapor concentrations necessary for nasal pungency or eye irritation (i.e., trigeminal) detection [17], the extent of interaction for an ester pair in a biophase is not likely to be more than 1 or 2 % [29]. Albeit the lack of an identical strategy and analysis between the 1-butanol/2-heptanone and the butyl acetate/toluene studies limits a direct comparison, the different chemical contrast between the alcohol and the ketone, compared to that of the acetate and the alkylbenzene, might have driven a dissimilar outcome (cf.…”
Section: Introductionmentioning
confidence: 99%
“…A problem in studies involving nicotine as an intranasal stimulant is that activation of trigeminal fibers may occur not only as a consequence of a single stimulus of nicotine, but in addition the concentration of nicotine in the nasal mucosa may build up due to repetitive stimulation, resulting in a sensory summation [Cometto-Muniz et al, 2004]. To avoid or minimize the so called temporal summation of irritation, we stimulated with relatively long interstimulus intervals (20 s) and interblock intervals (99.2 s) [Hummel and Livermore, 2002;Hummel et al, 2003b].…”
Section: Com]mentioning
confidence: 99%
“…We start with the psychometric plots obtained from the probability of sensory irritation detection, Q, of a given VOC as a function of its gaseous concentration, log P with P in ppm (Cometto-Muñiz et al, 1999;2001a;2002;2004a;2004b;2007b;2008;Cain et al, 2006). As for the determination of thresholds, this involves a panel of human subjects.…”
Section: The Psychometric Plotsmentioning
confidence: 99%
“…Several studies of sensory irritation thresholds (NPTs and EITs) from mixtures of VOCs have shown various levels of additivity that, to a first approximation, are not-too-far from complete additivity (Nielsen et al, 1988;Cometto-Muñiz et al, 1997;1999;2001a;2004a;2004b). So are results from studies on ODTs 2005b;Wise et al, 2007;Miyazawa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%